CONTRIBUIÇÕES DO PROJETO PANC PARA A FORMAÇÃO DO ALUNO PESQUISADOR - Rozemeire Corrêa da Silva (2020)
This research reports the proposal and the results of the Project Contributions of the PANC Project for the Training of Researcher Students, which was developed at the State School Maestro Frederico Liebermann, and involved the participation of students from the 3rd grade of High School. The objective of the project was to develop interdisciplinary practices associated with active methodologies to identify, recognize and study the PANC found around the school in order to provide innovative knowledge that includes self-interpretation, personal formulation, knowing how to think and learn to learn; understand that food plants can help solve the problem of hunger in Brazil and in the world. After the implementation of the PANC project, as a final product, a book was produced that presents the planning of all interdisciplinary activities and an account of the experience developed at the school, highlighting the most conventional non-conventional food plants found in the Bairro Monte Castelo region. The research had a qualitative research-action approach. For data collection, photographic records, data collection forms were used, and for data analysis, tasks, essay texts and questionnaires were used. We can highlight as results, the greater interaction between students, an evolution in resourcefulness, writing, participation in relation to the disciplines involved, thus contributing to the formation of more autonomous, safe and prepared students to carry out new research, which signals that the proposal interdisciplinary associated with the use of active methodologies contributed in Chemistry to the identification of the chemical composition of some substances present in PANC, associating the structural formula of at least one of its organic compounds to organic functions; in Biology with the study of its taxonomy and which part of the PANC can be consumed; in Portuguese with the production of scientific and essay texts; in Geography with the study of the delimited region, objectives of Sustainable Development, study of hunger in the world and in Brazil; in Computing research on trusted sites and studies on PANC. Keywords: Educating through research; Non-conventional food plants; active methodologies; student researcher and interdisciplinarity.